Smart Cooking and Kitchen Safety Using Arduino Nanotechnology and Voice Recognition - Jum, Jumriati; Abdul Latief; Imran Taufiq (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The purpose of this research encompasses two primary objectives: (1) Designing a smart cooking and kitchen safety system using Arduino Nanotechnology and voice recognition, and (2) Implementing these technologies in practical applications for smart cooking and kitchen safety. The aim is to develop a kitchen security system that employs Arduino Nano and voice recognition to automatically control conventional LPG stoves with on-off functionality. Data collection methods included observation, interviews, and literature review. Cooking tests were conducted with chicken curry, vegetable soup, and tuna, each cooked three times to determine average cooking times. Cooking 2 kg of chicken took an average of 35.38 minutes, with a maturity level delay of 18 minutes, while 1 kg of chicken took 20 minutes, with an 8-minute delay. For 20 portions of vegetable soup, the average cooking time was 32.20 minutes, with a 7-minute delay, and for 5 portions, it was 15 minutes, with a 4-minute delay. Cooking 2 kg of tuna took an average of 26 minutes, with a 16-minute delay, and 1 kg took 13.25 minutes, with a 5-minute delay. Voice command testing showed a high success rate at distances ranging from 10 cm to 70 cm. The confusion matrix results indicated that the model accurately detected successful commands with high precision (88.89%) and good recall (81.63%). However, the model had difficulty identifying failed commands, achieving only 2 true negatives out of 20 negative data points.